A Bibliometric Analysis of COVID-19 Researches: Omicron Variant - Husnul Khuluq; Tri Cahyani Widiastuti; Dwiki Fitri (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The aims of this research were to analyse the omicron variant COVID-19 literature published during the COVID- 19 pandemic and to guide future research relating to this variant. From 2021, November 26th to 2022, January 31th , the Pubmed (pubmed.gov) all databases collection was searched for publications related to omicron variant of COVID-19. The keywords used during this search were (omicron sars cov and (omicron covid-19). Exported Microsoft Excel files, Bibliometrics indicator analysis was performed using Bibliometric/Biblioshiny, a web interface application accessed using R-Studio. In total, 262 publications related to omicron varian of COVID- 19 were identified. In these publications, the most active author, journal, country and organisation were Wang L, Nature, China and University Of Oxford, respectively. The most commonly used keywords were humans, sars-cov-2, covid-19, mutation, covid-19 vaccines, spike glycoprotein coronavirus, adult, animals, covid-19/epidemiology/virology and antibodies viral/immunology. This Bibliometric analysis is helpful for mapping studies related to the omicron variant of COVID- 19. This article provides an overview of further researches related to omicron variant of COVID- 19 For example, by searching for keywords, this variant is associated with gender, spike glycoprotein coronavirus and mutation.